1994
DOI: 10.1002/ppul.1950180404
|View full text |Cite
|
Sign up to set email alerts
|

The absorption and effect of dietary supplementation with omega‐3 fatty acids on serum leukotriene B4, in patients with cystic fibrosis

Abstract: The substitution of omega-3 (n-3) fatty acids for omega-6 (n-6) fatty acids generates eicosanoids with diminished inflammatory effects. As the lungs of patients with cystic fibrosis (CF) are in a state of chronic inflammation in which increased amounts of eicosanoids are found, n-3 supplementation may reduce this level of inflammation and result in clinical improvement. The absorption and clinical effects of n-3 vs. n-6 fatty acids in CF were measured in a prospective, randomized, double-blind, crossover study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 58 publications
1
31
0
3
Order By: Relevance
“…This is corroborated by our data demonstrating that the administration of DHA, and not of precursor fatty acids, is required to correct the lipid abnormality as well as the pathologic changes observed in cftr Ϫ͞Ϫ mice. Formulations containing DHA (e.g., fish oil) have been given to CF patients in an effort to down-regulate AA levels and decrease inflammation (31)(32)(33). No statistically significant clinical improvements were found in these studies between control and CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by our data demonstrating that the administration of DHA, and not of precursor fatty acids, is required to correct the lipid abnormality as well as the pathologic changes observed in cftr Ϫ͞Ϫ mice. Formulations containing DHA (e.g., fish oil) have been given to CF patients in an effort to down-regulate AA levels and decrease inflammation (31)(32)(33). No statistically significant clinical improvements were found in these studies between control and CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…The fi ndings are representative of at least three independent experiments. by guest, on May 9, 2018 www.jlr.org Downloaded from several of these trials (39)(40)(41). More extensive studies in animal models and CF patients are required to confi rm these early observations.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference is unclear. Human trials ( 39 ) have shown differences in metabolism using EPA alone or combinations of EPA and DHA ( 29,30,40,41 ). However, the individual effects of EPA and DHA are diffi cult to disaggregate, as supplementation with either of these fatty acids increases concentrations of the other.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that n-3 fatty acids supplementation improve the clinical status of patients with rheumatoid arthritis [32]. In CF, n-3 fatty acid administration decreased serum LTB 4 [33, 34]. n-3 Fatty acids exert anti-inflammatory properties competing with n-6 FA in the biosynthesis of inflammatory products and affecting cellular transcriptional process.…”
Section: Lipids and Growthmentioning
confidence: 99%